A relevância da formação ética na educação profissional e tecnológica nos cursos de ensino médio integrado do IFPA Campus Belém - FERREIRA, Willi Jansen (2020)
This professional master's article from the Graduate Program in Professional and Technological Education (PROFEPT) aims to discuss the relevance of ethical training as an integral part of Professional and Technological Education (EPT) in the technical cour ses of Integrated High School (EMI) of the Belém Campus of the Federal Institute of Pará (IFPA), and is linked to the line of research: educational practices in professional and technological education. It also considers what ethical training is, its provi sion in educational laws and other documents, and how training has been offered at that Campus. It also discusses the interfaces between ethics and the dimensions of individual and collective responsibility within the scope of professional practices and ci tizenship. This is a theoretical study that used interviews with teachers and questionnaires to students. The pedagogical praxis related to ethical training is built on the outline of three EMI concluding courses: mechanics, telecommunications and electron ics. The analyzes and discussions were built based on the theoretical dialogue with Aristotle and Kant and the studies of Brazilian researchers such as Pedro Goergen, Maria Menin et al. Also noteworthy are Marise Ramos and Demerval Saviani, both theorists of EPT. The problematization was elaborated: what are the curricular bases that anchor the ethical training of EMI in the courses of the IFPA Campus Belém? We started from the hypothesis that the academic community would be inclined to consider the value o f ethical training if it is focused on citizenship and professional performance. Thus, it was found in the research, because the raison d'être of such training would occur in the construction of the bases of citizenship and work, allowing a good profession al performance, and that such ethical training implies a significant teaching activity of a discursive reflective character. that enables the conscious and transforming participation of society. Final considerations point to the fact that such training is urgent and necessary and that it must be the main purpose of education. Finally, our educational product are interactive didactic sequences, as these are adapted to the very nature of ethics and philosophy with regard to critical and reflective discussions